2000
DOI: 10.1016/s1010-7940(00)00584-4
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary thromboendarterectomy in patients with chronic thromboembolic pulmonary hypertension: hemodynamic characteristics and changes✩

Abstract: None of the variables considered was correlated with early death or functional nonsuccess. Neither preoperative severity of pulmonary hypertension nor degree of cardiac failure influenced the outcome of the operation. PTE leads to hemodynamic recovery even in very compromised patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
9

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 18 publications
1
56
0
9
Order By: Relevance
“…Thus, therapeutic strategies for management of RV contractile failure have concentrated on maneuvers to reduce RV afterload, such as pulmonary thromboendarterectomy or fibrinolysis in pulmonary embolism [6,7], inhaled nitric oxide following cardiopulmonary bypass or cardiac transplant [4], and on use of positive inotropic agents such as dobutamine. While there is no question that global RV ejection fraction sometimes improves with such therapeutic interventions, response to these interventions is highly variable.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, therapeutic strategies for management of RV contractile failure have concentrated on maneuvers to reduce RV afterload, such as pulmonary thromboendarterectomy or fibrinolysis in pulmonary embolism [6,7], inhaled nitric oxide following cardiopulmonary bypass or cardiac transplant [4], and on use of positive inotropic agents such as dobutamine. While there is no question that global RV ejection fraction sometimes improves with such therapeutic interventions, response to these interventions is highly variable.…”
Section: Introductionmentioning
confidence: 99%
“…The gold standard treatment of choice is pulmonary endarterectomy (PEA) surgery. Distal disease, whether vasculopathic or small vessel thrombotic, is a major risk factor for poorer outcome [1][2][3]. It has, however, been demonstrated that patients with high pulmonary vascular resistance (PVR) can still potentially benefit from operative intervention.…”
mentioning
confidence: 99%
“…Similarly, in a large series of 500 patients with CTEPH who underwent PEA, Jamieson et al reported that patients with a preoperative PVR of >1000 dyne·s·cm-5 had a significantly higher mortality rate than did those with a preoperative PVR of <1000 dyne·s·cm-5 (10.1% vs. 1.4%, respectively; P<0.0001) [18,19]. Although D' Armini et al reported that PEA leads to hemodynamic recovery even in severely compromised patients with CTEPH; the balance of evidence indicates that a high preoperative PVR has an unfavorable effect on the outcome after PEA [20].…”
Section: Discussionmentioning
confidence: 99%